1998
DOI: 10.1530/eje.0.1390337
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin secretion and its dopamine inhibitory control in rat fetuses

Abstract: This study has determined in rats the ontogenetic schedule of the onset of pituitary prolactin (PRL) synthesis and release as well as of the establishment of the dopamine (DA) inhibitory control of PRL secretion. RIA recognized PRL traces in the pituitary at the 18th embryonic day (E18), although a clearly detectable amount of this hormone was first measured at E20, suggesting the onset of PRL synthesis. The PRL level in the pituitary increased significantly by E22, in females to a higher extent than in males.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Dopamine is the main inotropic pharmacological agent used to support blood pressure in neonates, and it is likely that it has a similar function physiologically. DA within the brain regulates the proliferation of neuron progenitor cells [24], but the delineation of roles for circulating DA in the fetus have, as yet, been limited to the regulation of pituitary prolactin secretion [25], and to the control of the development of cardiomyocytes, and renal tubular epithelial cells [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is the main inotropic pharmacological agent used to support blood pressure in neonates, and it is likely that it has a similar function physiologically. DA within the brain regulates the proliferation of neuron progenitor cells [24], but the delineation of roles for circulating DA in the fetus have, as yet, been limited to the regulation of pituitary prolactin secretion [25], and to the control of the development of cardiomyocytes, and renal tubular epithelial cells [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…These data were obtained with high-performance liquid chromatography with electrochemical detection when studying either the mediobasal hypothalamus, dissected at E21, or the primary cell culture of this region taken at E17 and maintained for 7 days . Furthermore, dopamine production in the rat arcuate nucleus at E21 was sufficient to exert an inhibitory control of adenohypophysial prolactin secretion in fetuses (Melnikova et al, 1998), as in adults (Moore et al, 1985). Taking together the data obtained in this study and in our recent studies (Melnikova et al, 1998Balan et al, 2000), it may be suggested that dopamine is synthesized in the arcuate nucleus of fetuses by nondopaminergic TH-or AADCpossessing neurons acting in concert .…”
Section: Ontogenic Trend In the Neuron Populations Possessing Dopaminmentioning
confidence: 99%
“…Furthermore, dopamine production in the rat arcuate nucleus at E21 was sufficient to exert an inhibitory control of adenohypophysial prolactin secretion in fetuses (Melnikova et al, 1998), as in adults (Moore et al, 1985). Taking together the data obtained in this study and in our recent studies (Melnikova et al, 1998Balan et al, 2000), it may be suggested that dopamine is synthesized in the arcuate nucleus of fetuses by nondopaminergic TH-or AADCpossessing neurons acting in concert . Namely, L-tyrosine is converted to L-dopa (Yoshida et al, 1963;Garcia-Sancho et al, 1975;Zoli et al, 1993;Vieira-Coelho and Soares-da-Silva, 1998).…”
Section: Ontogenic Trend In the Neuron Populations Possessing Dopaminmentioning
confidence: 99%
“…Indications for the involvement of dopamine in this regulation in the prenatal period were obtained by inhibiting D2 receptors on lactotropocytes using haloperidol, which led to significant increases in the blood prolactin concentration, accompanied by a decrease in the hypophysis [16]. Regulation manifest as the effect of haloperidol on rat fetuses after initial exclusion of the hypothalamus (because encephalectomy) or hypothalamus and hypophysis (by decapitation) showed that hypothalamic dopamine does indeed affect hypophyseal lactotropocytes.…”
Section: Differentiation Of Hypothalamic Dopaminergic Neurons In Situmentioning
confidence: 99%